Phenomena of corruption and money laundering: and causes and risks and their role in the financing of terrorism in Iraq and finding ways of treatment (Journal of Accounting and Financial Studies ( JAFS ), 2012)
Iraq  is Suffering nowadays from the criminal triad represented by the fiscal and administrative corruption, money laundering and terrorism, which are intertwined in a very related relations, as each of them support the other . Since the over growth has been one of its characteristics leaving behind a very dangerous negative effects whether it was social , economic or even political impacts . As a result , this trial is now represents a high risk that threatens the present and the future of Iraq . On the political , economic and social level , it is well to mention that the poor direct investment , the increasing rates of poverty , unemployment , inflation as well as the smuggling of goreign currency and oil , the stoppage of economic development and also the failure of the reconstruction process , structural imbalances with high crime rates ending with the destruction of social fabric and many other phenomena which were brought on by the criminal triad against the weakness of laws and legislation , in addition of the weakness of fiscal , monetary and commercial policies . moreouer , the absence of the logical visions of people whom are in cgarge in handling and solving this criminal triad at some extent . Therefore this research come to highlight the intertwined this relation among the elements of the criminal triad as well as the reasons of overgrowth to such phenomena in Iraq and exposing its political , economic and social risks and not forgetting the proposed strategy in facing these phenomena .